(untitled) (The Pakistan Development Review, 2016)
Despite agriculture’s importance in terms of its relationship to poverty and welfare of the poorest households, the government finds it increasingly difficult to find the fiscal space for budgetary allocations for agriculture and agricultural RD. We hypothesise that expansion of expenditures on agriculture is possible in the short to medium run with a combination of reallocations and new taxation. We argue that existing spending aimed towards the agriculture sector includes very large outlays on implicit subsidies that are largely unproductive. These costs include: subsidisation of gas for fertiliser plants, which approach Rs 48 billion in gas subsidies to fertiliser companies; the full costs of the infrastructure and operation and maintenance of the irrigation system, which amount to Rs 166 billion per year; and losses on wheat procurement, which have been about Rs 25 billion recently. On the taxation side, while agricultural producers are not currently liable to pay tax on income, they do however pay indirect taxes on agricultural inputs. Using a Social Accounting Matrix (SAM), we estimate agricultural producer pay about Rs 61 billion, mostly from GST taxes on fertiliser. Using a Computable General Equilibrium model, we show that agriculture could contribute further with an income tax on agricultural income. With a ―low-rate-widebase‖ income tax of 15 percent on non-poor, medium and large farms, as much as Rs 130 billion could be raised, enough to cover, for example, a sizable portion of the operation and maintenance cost of the irrigation system. JEL Classifications: D58, E16, H20, H22, H23, Q10 Keywords: Agriculture, Fiscal Policy, Subsidies, Taxation, General Equilibrium, Social Accounting Matrix, Pakistan